2019
DOI: 10.21037/jtd.2019.06.30
|View full text |Cite
|
Sign up to set email alerts
|

Single-center experience of extracorporeal membrane oxygenation mainly anticoagulated with nafamostat mesilate

Abstract: Background: Bleeding remains the chief concern during extracorporeal membrane oxygenation (ECMO). Recently, several studies proposed nafamostat mesilate (NM) as an alternative anticoagulant to heparin due to reduced bleeding complications and comparable thromboembolic episodes. The aim of this study was to evaluate the clinical outcomes of ECMO anticoagulated mainly with NM. Methods: This was a retrospective observational case series of patients who were placed on ECMO between January 2011 and December 2017 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…7 Nafamostat is reportedly associated with fewer bleeding complications during ECMO without increasing the incidence of thromboembolic episodes. 8 Another recent report showed that nafamostat not only had anticoagulant effects but also potential anti-inflammatory and antiviral effects against COVID-19. 4 In the present case, circuit thrombosis was suppressed with the combination therapy, probably because of these anticoagulant and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Nafamostat is reportedly associated with fewer bleeding complications during ECMO without increasing the incidence of thromboembolic episodes. 8 Another recent report showed that nafamostat not only had anticoagulant effects but also potential anti-inflammatory and antiviral effects against COVID-19. 4 In the present case, circuit thrombosis was suppressed with the combination therapy, probably because of these anticoagulant and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Nafamostat is reportedly associated with fewer bleeding complications during ECMO without increasing the incidence of thromboembolic episodes 8 . Another recent report showed that nafamostat not only had anticoagulant effects but also potential anti‐inflammatory and antiviral effects against COVID‐19 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Of these records 4.031 records were excluded for not meeting inclusion criteria for titles and abstracts, leaving 51 potentially relevant articles. Among these articles we identified 25 conference abstracts , 3 studies in which patients were switched between intervention and control group [41][42][43] and 5 studies that investigated nafamostat mesilate but not DTI versus heparin [44][45][46][47][48]. These 33 studies were excluded, leaving 18 studies for inclusion into data synthesis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Similarly, Han et al observed more bleedings with UFH, but 3 cases of intracerebral hemorrhage with NM. Survival was higher in the NM group (38.2% vs. 13.6%) and heparin was found to be the only independent predictor of bleeding complications [ 20 ]. Conflicting results were presented in another retrospective study based on propensity-matched data.…”
Section: Resultsmentioning
confidence: 99%